Research on Electrical Energy Consumption Efficiency Based on GM-DEA - Mei Liu (Institute of Advanced Engineering and Science, 2014)
In today's environment which emphasis on energy efficiency, predicting the trend of electrical energy consumption efficiency, and researching the efficient operation model of power industry has practical significance. By establishing GM-DEA method system, we use GM model to predict four inputs and output indicators in 2011 and 2012 in Beijing first, and then use DEA to give predicting years a reasonable analysis for the efficiency of energy consumption. The result shows that efficiency of electrical energy consumption in Beijing is gradually increasing, GM-DEA model can analyze the trend of the efficiency effectively in advance, and it provides a scientific basis for the rapid development of power industry.